Species-Specific Variation in Abscisic Acid Homeostasis and Responses Impacts Important Traits in Crassocephalum Orphan Crops - Adedeji-Badmus, Adebimpe N.; Schramm, Sebastian; Gigl, Michael; Iwebema, Williams; Albertos, Pablo; Dawid, Corinna; Sieberer, Tobias; Poppenberger, Brigitte (Frontiers in Plant Science, 2022)
Crassocephalum rubens and C. crepidioides are plant species native to Africa, but grow in most tropical and subtropical regions of the world. They are rich in vitamins, minerals, and essential oils and are traditional leafy vegetable and medicinal plants in Sub-Saharan Africa. The plants are still mainly collected from the wild, but shall be taken into cultivation and an important aim in the domestication of these species is to improve traits that are relevant for crop production. Here seed formation and germination capacities in C. crepidioides and C. rubens were investigated and it was found that C. crepidioides exhibits a higher level of seed dormancy, which could be broken with light, and was correlated with higher amounts of abscisic acid (ABA), a plant hormone that promotes seed dormancy. ABA is also very well-known for its roles in abiotic stress tolerance, and it is shown that tetraploid C. crepidioides exhibits a higher level of resistance against drought and heat stress than diploid C. rubens, traits that will benefit the cultivation of these plants, in particular in rain-fed cropping systems. The potential of Crassocephalum to improve nutrition and increase the resilience of marginal cropping systems in Africa is discussed.